Synergistic Enzyme Cocktail to Enhance Hydrolysis of Steam Exploded Wheat Straw at Pilot Scale - Agrawal, Ruchi; Semwal, Surbhi; Kumar, Ravindra; Mathur, Anshu; Gupta, Ravi Prakash; Tuli, Deepak K.; Satlewal, Alok (Frontiers in Energy Research, 2018)
Multiple enzymes are required for efficient saccharification of lignocellulosic biomass and no wild type organism is capable of producing all enzymes in desired levels. In this study, steam explosion of wheat straw was carried out at pilot scale and a synthetic enzyme mixture (EnzMix) was developed by partially replacing the cellulase with critical dosages of commercially available accessory enzymes (β-glucosidase, xylanase and laccase) through central composite design. Highest degree of synergism (DS) was observed with β-glucosidase (1.68) followed by xylanase (1.36). Finally, benchmarking of EnzMix (Celluclast, β-glucosidase and xylanase in a protein ratio of 20.40: 38.43: 41.16, respectively) and other leading commercial enzymes was carried out. Interestingly, saccharification improved by 75% at 6h and 30% at 24h, respectively in comparison of control. By this approach, 25% reduction in enzyme dosage was observed for obtaining the same saccharification yield. Thus development of enzyme cocktail is an effective and sustainable approach for high saccharification efficiency.